Presynaptic Release-Regulating Alpha2 Autoreceptors: Potential Molecular Target for Ellagic Acid Nutraceutical Properties - Isabella Romeo; Giulia Vallarino; Federica Turrini; Alessandra Roggeri; Guendalina Olivero; Raffaella Boggia; Stefano Alcaro; Giosuè Costa; Anna Pittaluga (Antioxidants, 2021)
Polyphenol ellagic acid (EA) possesses antioxidant, anti-inflammatory, anti-carcinogenic, anti-diabetic and cardio protection activities, making it an interesting multi-targeting profile. EA also controls the central nervous system (CNS), since it was proven to reduce the immobility time of mice in both the forced swimming and the tail-suspension tests, with an efficiency comparable to that of classic antidepressants. Interestingly, the anti-depressant-like effect was almost nulled by the concomitant administration of selective antagonists of the noradrenergic receptors, suggesting the involvement of these cellular targets in the central effects elicited by EA and its derivatives. By in silico and in vitro studies, we discuss how EA engages with human α2A-ARs and α2C-AR catalytic pockets, comparing EA behaviour with that of known agonists and antagonists. Structurally, the hydrophobic residues surrounding the α2A-AR pocket confer specificity on the intermolecular interactions and hence lead to favourable binding of EA in the α2A-AR, with respect to α2C-AR. Moreover, EA seems to better accommodate within α2A-ARs into the TM5 area, close to S200 and S204, which play a crucial role for activation of aminergic GPCRs such as the α2-AR, highlighting its promising role as a partial agonist. Consistently, EA mimics clonidine in inhibiting noradrenaline exocytosis from hippocampal nerve endings in a yohimbine-sensitive fashion that confirms the engagement of naïve α2-ARs in the EA-mediated effect.